Nordic contributions in IS research : 7th Scandinavian Conference on Information Systems, SCIS 2016 and IFIP8.6 2016, Ljungskile, Sweden, August 7-10, 2016, Proceedings /: 7th Scandinavian Conference on Information Systems, SCIS 2016 and IFIP8.6 2016, Ljungskile, Sweden, August 7-10, 2016, Proceedings. (2016) - Unknown
No abstract available